Penerapan Posisi Miring Kiri terhadap Peningkatan Tekanan Darah Pasca Spinal Anastesi pada Pasien Post Operasi - Nur Rohmah; Wijanarko Heru Pramono (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Post-spinal hypotension in patients recovering from cesarean section remains a common hemodynamic problem during the early recovery phase because sympathetic nerve blockade can reduce systemic vascular resistance and venous return to the heart. This study aims to analyze the effectiveness of the left lateral recumbent position in improving blood pressure following spinal anesthesia in postoperative patients at RSI PKU Muhammadiyah Pekajangan. The study employed a descriptive-analytical design using a pre-test and post-test case study approach involving five post-cesarean section patients experiencing postoperative hypotension. Data collection was conducted by measuring blood pressure before and after the left lateral recumbent position intervention for 10–15 minutes using a calibrated digital blood pressure monitor. The results showed an increase in systolic blood pressure of 15–20 mmHg and diastolic blood pressure of 10–12 mmHg in all participants, accompanied by improvement in clinical complaints such as dizziness and weakness. The left lateral recumbent position was proven to help improve hemodynamic stability through enhanced venous return and cardiac output, thereby potentially serving as a safe, simple, and effective nonpharmacological nursing intervention in the management of post-spinal anesthesia recovery.